Games people play game theory in life, business, and beyond - Teaching Company (Chantilly, VA : Teaching Company, 2008)
Presents lectures (each 30 minutes in length) by Scott P. Stevens, Professor of Computer Information Systems and Management Science at James Madison University, based on his courses in game theory.
Part 2: Disc 3. Lecture 13. Whom can you trust? ; Lecture 14. Encouraging productivity, incentive schemes ; Lecture 15. Persistence of memory, repeated games ; Lecture 16. Does this stuff really work? ; Lecture 17. Tragedy of the commons ; Lecture 18. Games in motion, evolutionary game theory -- Disc 4. Lecture 19. Game theory and economics, oligopolies ; Lecture 20. Voting, determining the will of the people ; Lecture 21. Auctions and the winner's curse ; Lecture 22. Bargaining and cooperative games ; Lecture 23. Game theory and business, co-opetition ; Lecture 24. All the world's a game.
Part 1 and Part 2 each consist of 2 DVDs.
"Course no. 1426"
Lecturer: Professor Scott P. Stevens.
DVD.
Keywords: Educational films; Game theory; Game theory -- Study and teaching